1994
DOI: 10.1159/000217908
|View full text |Cite
|
Sign up to set email alerts
|

Study of a New Tumor Marker, CYFRA21-1, in Malignant and Nonmalignant Diseases

Abstract: The diagnostic value of a new tumor marker, CYFRA 21-1, was studied in the sera of 50 controls, 206 patients with benign diseases and 469 patients with malignancies. Fifty controls showed mean serum concentrations of 1.2 ± 0.5 ng/ml. Using 3.3 ng/ml as the cutoff, abnormal CYFRA levels were found in 13.1% of patients with benign diseases, mainly in those with liver cirrhosis (29.4%) or renal failure (20.8%), and in 44.4% (180/405) of patients with active cancer. Neither healthy subjects nor no evidence of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 10 publications
5
38
0
2
Order By: Relevance
“…In previous studies, 20 -30% of patients with one of these three benign diseases showed elevated levels of serum CYRFA 21-1 (Molina et al, 1994;Nakata et al, 1996). However, little is known about this tumour marker for breast cancer (Molina et al, 1994;Nakata et al, 2000;Giovanella et al, 2002;Rodriguez et al, 2002). According to serum CYFRA 21-1 levels at pre-and postoperation, the patients were divided into groups A, B, and C. Frequencies of recurrences were different between A and B (P ¼ 0.0312), A and C (P ¼ 0.0162), and A and B+C (P ¼ 0.007), but not B and C (P ¼ 0.1468), examined by w 2 test (Fisher's exact method).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In previous studies, 20 -30% of patients with one of these three benign diseases showed elevated levels of serum CYRFA 21-1 (Molina et al, 1994;Nakata et al, 1996). However, little is known about this tumour marker for breast cancer (Molina et al, 1994;Nakata et al, 2000;Giovanella et al, 2002;Rodriguez et al, 2002). According to serum CYFRA 21-1 levels at pre-and postoperation, the patients were divided into groups A, B, and C. Frequencies of recurrences were different between A and B (P ¼ 0.0312), A and C (P ¼ 0.0162), and A and B+C (P ¼ 0.007), but not B and C (P ¼ 0.1468), examined by w 2 test (Fisher's exact method).…”
Section: Discussionmentioning
confidence: 86%
“…We also demonstrated in a previous report (Nakata et al, 2000) that serum CYFRA 21-1 has not only a high positive rate for breast cancer but also high specificity for breast cancer, that is, 22 patients with benign mammary disease did not show elevated levels of serum CYFRA 21-1. Molina et al (1994) also reported that only 4% (one of 25) of patients with benign mammary disease had elevated levels of serum CYFRA 21-1.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations